Extended criteria for liver transplantation in hepatocellular carcinoma. A retrospective, multicentric validation study in Belgium. (June 2020) - Degroote, Helena; Callebout, Eduard; Iesari, Samuele; Dekervel, Jeroen; Schreiber, Jonas; Pirenne, Jacques; Verslype, Chris; Ysebaert, Dirk; Michielsen, Peter; Lucidi, Valerio; Moreno, Christophe; Detry, Olivier; et al.
Abstract: Background: Recent studies indicate that a group of patients with cirrhosis receiving a liver transplantation for hepatocellular cancer (HCC) beyond the Milan Criteria (MC) can achieve a similar outcome compared to patients within these criteria. This study aims to investigate the value of the Asan critera (AC), up-to-7 criteria (UT7), French alpha-foetoprotein (AFP) model and Metroticket 2.0 (MT2.0) model compared to the MC. Methods: 526 patients transplanted for non-metastatic HCC were analyzed. Patient groups within and beyond MC and extended criteria were determined according to radiological assessment and AFP value at listing. Results: Overall survival (OS) and recurrence (RR) rates were similar between patients within MC and all extended criteria. Five-year OS within MC was 71.3% compared to 70.9% for AC, 71.4% for UT7, 69.7% for AFP-model and 71.0% for MT2.0 criteria. Five-year RR within MC was 12.3% compared to 13.5% for AC, 13.0% for UT7, 14.3% for AFP-model and 13.2% for MT2.0 criteria. Patients beyond MC but within the extended criteria had tendency towards higher recurrence. Conclusions: All validated extended criteria (AC, UT7, AFP-model and MT2.0) could be proposed as alternatives to the MC with similar outcome. Prospective data are awaited to assess recurrence beyond MC.